2012
DOI: 10.1002/ijc.27843
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of three lynch syndrome cohorts confirms the modifying effects of 8q23.3 and 11q23.1 in MLH1 mutation carriers

Abstract: Two colorectal cancer (CRC) susceptibility loci have been found to be significantly associated with an increased risk of CRC in Dutch Lynch syndrome (LS) patients. Recently, in a combined study of Australian and Polish LS patients, only MLH1 mutation carriers were found to be at increased risk of disease. A combined analysis of the three data-sets was performed to better define this association. This cohort-study includes three sample populations combined totaling 1,352 individuals from 424 families with a mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…First, information on hereditary nonpolyposis colorectal cancer was not collected across studies, hence, we were not able to examine directly if added common genetic risk loci would improve risk prediction for subjects with rare-high-penetrance mutations. Previous works have found the modifying effects of common SNPs in carriers of mismatch repair gene mutations; 36 however these results were not replicated in other studies. 37, 38 Using family history as a surrogate, we found that the genetic risk score of common loci remains to be significantly associated with increased risk of CRC in both men and women with a positive family history of CRC (results not shown), suggesting common genetic loci improve risk prediction in this group.…”
Section: Discussionmentioning
confidence: 62%
“…First, information on hereditary nonpolyposis colorectal cancer was not collected across studies, hence, we were not able to examine directly if added common genetic risk loci would improve risk prediction for subjects with rare-high-penetrance mutations. Previous works have found the modifying effects of common SNPs in carriers of mismatch repair gene mutations; 36 however these results were not replicated in other studies. 37, 38 Using family history as a surrogate, we found that the genetic risk score of common loci remains to be significantly associated with increased risk of CRC in both men and women with a positive family history of CRC (results not shown), suggesting common genetic loci improve risk prediction in this group.…”
Section: Discussionmentioning
confidence: 62%
“…Compared with patients with an MLH1 mutation, for example, those with an MSH2 mutation have a higher risk of a noncolorectal malignancy and those with an MSH6 mutation have a higher risk of endometrial cancer (35,36). Patients with an MLH1 mutation, in turn, are more likely to develop colorectal cancer at a young age in the presence of specific risk alleles (37).…”
Section: Pathogenesis Of Msi In Colorectal Cancersmentioning
confidence: 99%
“…In a recent study, Talseth-Palmer et al 6 conducted a pooled analysis by combing the studies by Wijnen et al 3 and Talseth-Palmer et al 4 to investigate the role of seven SNPs from six independent loci on CRC risk for MMR gene mutation carriers. They reported that carriers of the C-allele of rs16892766 (8q23.3) and the C-allele of rs3802842 (11q23.1) are at increased risk of CRC for MLH1 mutation carriers.…”
mentioning
confidence: 99%
“…This is the design used by the study of Talseth-Palmer et al 6 While this retrospective design overcomes the limitations of case-control and prospective cohort studies described above, it introduces additional problems given MMR gene mutation carriers will not be random with respect to CRC status overall, and with respect to age. The sampling of MMR gene mutation carriers does not represent a true cohort, and standard analysis methods (such as Cox regression used by Talseth-Palmer et al…”
mentioning
confidence: 99%
See 1 more Smart Citation